2020
DOI: 10.1016/j.scitotenv.2020.140412
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of devices intended to reduce microfibre release during clothes washing

Abstract: The washing of synthetic clothes is considered to be a substantial source of microplastic to the environment. Therefore, various devices have been designed to capture microfibres released from clothing during the washing cycle. In this study, we compared 6 different devices which varied from prototypes to commercially available products. These were designed to either be placed inside the drum during the 20 washing cycle or fitted externally to filter the effluent wastewater discharge. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 41 publications
3
79
1
Order By: Relevance
“…Due to the potential for microfibers, both synthetic and non-synthetic, to cause ecological harm, upstream mitigation efforts are underway to reduce their input into the environment such as products that specifically address microfiber pollution by capturing fibers during the laundry wash cycle (in-drum and external devices) [38]), and strategies that address the greater problem of microplastic in our public waterways such as bans on plastic microbeads in personal hygiene products, single use plastic bans, efforts to improve waste infrastructure and management practices, consumer education campaigns and developing alternative compostable or PLOS ONE form of use of equipment for author [R.Z.M], but did not have any additional role in the funding, study design, data collection and analysis, decision to publish, or preparation of the manuscript. The specific roles of this author are articulated in the 'author contributions' section.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the potential for microfibers, both synthetic and non-synthetic, to cause ecological harm, upstream mitigation efforts are underway to reduce their input into the environment such as products that specifically address microfiber pollution by capturing fibers during the laundry wash cycle (in-drum and external devices) [38]), and strategies that address the greater problem of microplastic in our public waterways such as bans on plastic microbeads in personal hygiene products, single use plastic bans, efforts to improve waste infrastructure and management practices, consumer education campaigns and developing alternative compostable or PLOS ONE form of use of equipment for author [R.Z.M], but did not have any additional role in the funding, study design, data collection and analysis, decision to publish, or preparation of the manuscript. The specific roles of this author are articulated in the 'author contributions' section.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research has focused on methods for reducing microplastics generated during the washing process. The study for reducing the generation of MFs during laundry can be categorized into in-drum and external device approaches (McIlwraith et al 2019;Napper et al 2020). In-drum devices are placed inside the washing machine along with the garments to capture MFs and reduce friction, and external devices use a membrane to reduce MFs contained in the washing drainage.…”
Section: Discussionmentioning
confidence: 99%
“…The Guppyfriend, for example, is a fine mesh bag in which clothes can be placed for washing, while the Cora Ball traps the fibres that are released during washing. K€ arkk€ ainen and Sillanp€ a€ a (2021) found that these two devices reduced microfibres in the outlet of the washing machines by only 39% and 10%, respectively, while Napper et al (2020) measured a 54% reduction with the Guppyfriend bag. The latter authors concluded that the most effective device was the XFiltra, which, when fitted to the effluent water, reduced fibre release by 78%.…”
Section: Modification Of Washing Proceduresmentioning
confidence: 99%